Morphology and relationships of a new species of Henicops (Chilopoda: Lithobiomorpha) from New South Wales and Queensland, Australia - Edgecombe, Gregory D.; Hollington, Lauren M. (Zootaxa, 2005)
The henicopid centipede Henicops Newport, 1845, is common and widespread in wet forests in Australia and New Zealand. A new species of Henicops, H. washpoolensis, is widely distributed in northern New South Wales and southern Queensland, ranging into the wet tropics of north Queensland. Parsimony analysis of morphological characters identifies the monophyly of an Australasian group within Henicops relative to more distantly allied species from Lord Howe Island and New Caledonia. The most parsimonious cladograms unite the three species from southeastern Australia and New Zealand to the exclusion of congeners from Western Australia and north Queensland or unite all Australasian species to the exclusion of H. washpoolensis.